Predictive Preemptive Ad Hoc On-Demand Distance Vector Routing - Hacene, Sofiane Boukli; Lehireche, Ahmed; Meddahi, Ahmed (Malaysian Journal of Computer Science, 2006)
Routing protocols for ad hoc networks typically include mechanisms for route discovery and route maintenance. The performance of these protocols depends on the route maintenance mechanism they use. The movement of network nodes can cause routes to become unusable. A node on a route from a source to a destination may become unreachable from its predecessor node because of node movement. In this paper, we propose a predictive preemptive approach to route maintenance. Route maintenance is initiated when a link break is expected rather than waiting for the break to happen. To evaluate the approach, we have added it to the AODV routing protocol, and evaluated its impact on performance using detailed simulations. The simulation results show that the proposed approach can be expected to improve performance significantly. It can reduce communication overhead, decrease the number of breaks in active links, reduce end-to-end packet delays, and improve packet delivery ratio.